Job satisfaction and work discipline improve employee performance: a case study - Widigdo, Aslam Mei Nur; Ali, Nur (Jurnal Konseling dan Pendidikan, 2025)
Human resources are important in achieving the company's goals, especially with labor-intensive characteristics such as industrial manufacturing. PT.  DSI is one of Indonesia's automotive component manufacturing companies that has problems related to human resource productivity and rejected product ratios. This study examined the influence of job satisfaction and work discipline on the performance of factory employees at PT. DSI. This study uses a quantitative approach.  The population in this study were all PT DSI factory employees, totaling 185 people. Based on the Slovin formula with a sampling error of 5%, the sample size was 127 respondents. The sampling method is purposive sampling. The data analysis technique used Smart PLS 3.2.9 as a tool. The results show that job satisfaction has a positive significant effect on the performance of factory employees either directly or mediated by work discipline, work discipline has a positive significant effect on the performance of factory employees, and job satisfaction has a significant positive effect on work discipline. The strategic implication of this research is the need for management to increase supervision of employee work discipline both in fulfilling attendance and standard operating procedures, as well as the need to pay attention to employee satisfaction.